A comparison of the diversity and abundance of frugivorous butterflies (Lepidoptera: Nymphalidae) in Kubah National Park, Kuching and Kampung Temurang, Padawan, Sarawak - Mohamed Asri, Mohamed Saad (Universiti Malaysia Sarawak (UNIMAS), 2017)
Study on distribution and species composition of frugivorous butterflies is crucial especially to understand their distribution pattern and behavior because most of them are very sensitive to changes in environment. This research was conducted at two sites, Kubah National Park, Kuching (KNP) and Kampung Temurang, Padawan (KTP) for five sampling days which was held on 281 August 2016 to 15t September 2016 and 23rd October 2016 to 27th October 2016, respectively. The traps used during the sampling was baited trap which were placed above the ground and at canopy level of selected trees, installed using Single-Rope Technique and overripe pineapple used as baits. A total of 77 individuals from seven subfamilies and 33 species was recorded at KNP while KTP recorded a number of 33 individuals from seven subfamilies and 18 species. The most dominant nymphalids in KNP was Bassarona dunya monara with ten individuals while dominant species at KTP represented by three species from Satyrs, Mycalesis horsfieldi hermana, Mycalesis mnasicles mnasicles and Ragadia makuta umbrata with four individuals. Both sites recorded a significantly higher abundance of frugivorous butterflies at ground level compared to canopy level.